SIMULASI ALAT PENJARING IKAN OTOMATIS DENGAN PENGGERAK MOTOR SERVO CONTINUOUS, SENSOR JARAK HC-SR04 DAN TOMBOL, MENGGUNAKAN ARDUINO MEGA - Muhammad Akmal Mulyono (STEKOM PRESS, 2019)
The current harvesting system of fish is still not optimal and requires a lot of manpower. In every fish culture place, we can see that the fish netting system still uses manual nets, lots of people, and a long time. This affects turnover / income and profit from fish empowerment efforts. Therefore, to increase the efficiency of time, human power, turnover, and profit, this tool becomes a solution for each fish empowerment place. Because this tool is designed with an automatic system with continuous servo motor, proximity sensor HC-SR04, push button, with an arduino mega base. button as an input command, empowerment only needs to input into the button (push button) to start harvesting fish from aquaculture, so that this work becomes more efficient in time, manpower, and affects the increase in turnover and business profit.